Using iPods® and iPads® in teaching programs for individuals with developmental disabilities: A systematic review - Kagohara, Debora M.; van der Meer, Larah; Ramdoss, Sathiyaprakash; O’Reilly, Mark F.; Lancioni, Giulio E.; Davis, Tonya N.; Rispoli, Mandy; Lang, Russell; Marschik, Peter B.; Sutherland, Dean; Green, Vanessa A.; Sigafoos, Jeff (Research in developmental disabilities, 2013)
► Reviewed use of iPads® and related devices for teaching persons with developmental disabilities. ► Devices used to teach skills from five domains. ► Devices used to deliver prompts or access preferred stimuli. ► Results were largely positive. ► iPads® and related devices are viable for use in teaching this population. We conducted a systematic review of studies that involved iPods®, iPads®, and related devices (e.g., iPhones®) in teaching programs for individuals with developmental disabilities. The search yielded 15 studies covering five domains: (a) academic, (b) communication, (c) employment, (d) leisure, and (e) transitioning across school settings. The 15 studies reported outcomes for 47 participants, who ranged from 4 to 27years of age and had a diagnosis of autism spectrum disorder (ASD) and/or intellectual disability. Most studies involved the use of iPods® or iPads® and aimed to either (a) deliver instructional prompts via the iPod Touch® or iPad®, or (b) teach the person to operate an iPod Touch® or iPad® to access preferred stimuli. The latter also included operating an iPod Touch® or an iPad® as a speech-generating device (SGD) to request preferred stimuli. The results of these 15 studies were largely positive, suggesting that iPods®, iPod Touch®, iPads®, and related devices are viable technological aids for individuals with developmental disabilities.